URGENCY OF SOCIALIZATION REGULATION REGARDING ESTABLISHMENT OF VILLAGE REGULATIONS - Adhitya Widya Kartika (UNTAG Law Review, 2019)
A country in carrying out its duties and authorities should have a legal basis which is the legality of its authority. This is reinforced by the state of Indonesia has included a rule of law on the constitution. While the village government is a part of the Indonesian state whose authority is one of which is regulated in the Law of the Republic of Indonesia Number 6 of 2014 concerning Villages. The village head is given the authority to form village regulations. Village regulations are expected to have solutions to village needs. Whereas in the formation of village regulations, their formation must be in accordance with the conditions of their formation. An obligation or regulation that is set to be enforceable or has a binding capacity should be regulated in a regulation which is a form of agreement between the government and the community. But there are provisions or regulations whose implementation rules are not to the last level. In fact there are provisions even though they have been enacted but there is no socialization so there are obstacles in their implementation. So it is important to socialize legal norms. Research on the urgency of socialization of legislation related to the formation of village regulations uses empirical legal research methods in which data can be obtained from the field or also referred to as socio legal research related to the formation and implementation of legislation related to village regulations